PENGARUH JUMLAH PENDUDUK, UPAH MINIMUM, DAN PENGELUARAN PEMERINTAH TERHADAP PENYERAPAN TENAGA KERJA DI JAWA BARAT - Kinanti Laras Arum, (2021)
West Java is one of the provinces with the largest population in Indonesia. This indicates that the number of labor force in West Java is also quite large, but not all of the existing workforce can be absorbed. This is because there is still a lack of available job opportunities and the quality of human resources is not enough to compete. This study aims to determine whether there is an effect of population, minimum wage and government spending on Labor Absorption in West Java. The research method used in this research is panel data regression analysis and quantitative descriptive analysis supported by existing quantitative data. The data is processed by using software eviews 9. The results of this study indicate that the population and the minimum wage affect employment, while government spending has no effect on employment. Keyword : Population, Wages, Government Spending, Labor